Considerations way of Iben Ashour - Al Mansouri, Samaya bint Samir (Journal of Islamic Sciences, 2019)
This study handles the matter of considerations as assumed by Iben Ashour, where I adopt the analytical descriptive approach though presenting such process followed by Iben Ashour, the study shows his way of expressing it, the type of consideration he handled and some examples of each type, I have divided the study into two sections, theoretical and applied, I included in the theoretical section, two themes, the first one is in the concept of the consideration under which two requirements, while the second theme speaks about taking care of consideration by Iben Ashour, laying under this theme two requirements. As for the applied study; there are two themes herein, the first theme, I handles the Quranic evidences relating to the sections of the consideration where it contains five requirements, while the second theme hereof handles other subjects that Iben Ashour included within the consideration matter, this study is concluded into approximatly twenty six pages.